2018 Smart City Symposium Prague (SCSP) 2018
DOI: 10.1109/scsp.2018.8402651
|View full text |Cite
|
Sign up to set email alerts
|

Framework for planning the mobility service based on autonomous vehicles

Abstract: Abstract-Autonomous vehicles (AVs) facilitate alteration in the passenger transportation. Shared, demand-driven mobility services based on small-capacity AVs emerge in urban areas. In order to provide highly personalized services and to enhance the acceptance of AVs, the user expectations are to be revealed. The research question is what kind of information is needed to plan various service types with the consideration of user expectations and operational constraints. Accordingly, the planning functions, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
21
1
1
Order By: Relevance
“…Similar results were also documented in a report on "The Challenge and Impact of Autonomous Vehicle Development in Taiwan: Socioeconomic Impact" [15], which indicated that the benefits were: reduced traffic congestion, enhanced mobility for the elderly and disabled, environmental friendliness, and lowered fuel consumption, while the potential risks included lack of legal regulation, technical safety, privacy, and data misuse. Lastly, several studies have found age to be associated with the intention for adoption of autonomous vehicles, with younger people expressing higher interest [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also documented in a report on "The Challenge and Impact of Autonomous Vehicle Development in Taiwan: Socioeconomic Impact" [15], which indicated that the benefits were: reduced traffic congestion, enhanced mobility for the elderly and disabled, environmental friendliness, and lowered fuel consumption, while the potential risks included lack of legal regulation, technical safety, privacy, and data misuse. Lastly, several studies have found age to be associated with the intention for adoption of autonomous vehicles, with younger people expressing higher interest [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The other two areas selected are the relatively well-researched domains of AI application, autonomous vehicles, and smart homes. As two of the most rapidly developed domains of HLMI application, the benefits and concerns of the autonomous vehicle and smart home as perceived by the public have been explored in some studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but opinions of the benefits and concerns have seldom been discussed together and empirically examined. A secondary purpose of this present study, then, is to find out how positive benefits and potential concerns and risks play roles upon people's perception about autonomous vehicles and smart homes.…”
Section: Introductionmentioning
confidence: 99%
“…However, individual car use decreases by the introduction of a flexible shared AV service because similar service quality can be provided as by an individual car. Current car users' willingness to shift is the highest, as bikers' and pedestrians' willingness to shift are the lowest according to our previous study [29]. The number of cars decreases as less vehicle is enough to meet the needs.…”
Section: Impacts Of Alterationmentioning
confidence: 79%
“…In our previous studies [22,23], we performed a questionnaire survey to reveal user expectations. The main findings were:…”
Section: Planning Principlesmentioning
confidence: 99%
“…It is mentioned in several previous investigations that the level of automation trustworthiness influences the frequency of its introduction. [15][16][17][18][19]. Trust in terms of the psychological aspect means that the human or object acts as it was assumed [20][21][22].…”
Section: Related Workmentioning
confidence: 99%